Training Programs to Promote the Nursing Practice Skills of Overseas Qualified Nurses: A Scoping Review - Rina Shoki; Hitomi Suzuki; Erika Ota (Pacific Rim International Journal of Nursing Research, 2023)
For overseas qualified nurses, training is important for adaptation to the nursing practices in their new country. As a precursor to a systematic review, we conducted a scoping review to map the contents and outcomes of all training programs used to promote the ability of overseas qualified nurses to adapt to nursing practice in their host country. We conducted a scoping review based on the framework proposed by the Joanna Briggs Institute. The searched databases were PubMed, EMBASE, CINAHL PLUS, British Nursing Index (BNI), and Japan Medical Abstracts Society. The search was conducted in December 2021. Fourteen studies that met the eligibility criteria were included in this scoping review. The program contents included language, knowledge for nursing practice in the host country, and clinical practice. Language skills included pronunciation and culture-based communication needed in nursing practice, while knowledge for nursing practice provided what was needed in the actual setting. Outcomes were assessed by participant experience, useful aspects and challenges of the program, language communication skills, and nursing competencies. Regarding program effectiveness, in the 11 studies that reported program evaluation, one of the three experimental studies found significant improvement of the skills of the intervention group. Six other studies, which evaluated qualitatively, reported positive responses from the participants. Programs that provided content that enabled overseas qualified nurses to acquire the knowledge and skills required in the host country contributed to promoting their ability to adapt to nursing practice. Only three experimental studies were conducted, indicating a lack of evidence to assess the effectiveness of the program.